Visual syntax: a study of visual narrative promoting social unity through Petronas thematic television commercials / Khairulwafi Mamat - Mamat, Khairulwafi (2022)
The study concerns social unity promoted in the thematic television commercials produced by Petronas. The main focus of this study is to examine how visual and verbal, gesture, graphic style, storytelling and narrative reception; in order to promote social unity, portrayed by Petronas thematic television commercials. The study fascinates by the peculiarities and commonalities in advertising appeals among multicultural societies. In outlining the study, a quantitative method used to collect evident based on the questionnaire given to the respondents. The questionnaire set was constructed based on the variable that set for this study. Measurement of the collected data evaluated using Likert scale. Findings gathered from the collected data supported five hypotheses, as analysis showed that there was a strong correlation between the visual and verbal approach, the gesture approach, the graphic style approach and the storytelling approach. The outcome of this study also found out that; the fifth hypotheses; narrative reception has a mediation effect on all of the procedures mention before. Besides, the strengthening of the storyline is an aspect that needs the most attention, as agreed with most respondents. Thus, the use of visual syntax to assist narrative performances is indirectly involving elements of style. Lastly, as a conclusion, this study concludes that in low-context culture, television commercials would be more likely to contain complete information to the audience.